Ammonium acid urate urolithiasis in anorexia nervosa: a case report and literature review. Issue 5 (31st March 2017) - Fukai, Mina; Hirosawa, Tetsu; Nakatani, Hideo; Muramatsu, Tomoko; Kikuchi, Mitsuru; Minabe, Yoshio
Key Clinical Message: Ammonium acid urate urolithiasis is a quite rare condition. Our literature review of ammonium acid urate urolithiasis suggests that ammonium acid urate urolithiasis should be regarded as a general medical complication related to anorexia nervosa, and purging by laxative abuse might be a crucially important risk. Abstract : Ammonium acid urate urolithiasis is a quite rare condition. Our literature review of ammonium acid urate urolithiasis suggests that ammonium acid urate urolithiasis should be regarded as a general medical complication related to anorexia nervosa, and purging by laxative abuse might be a crucially important risk.